PENGARUH KUALITAS AUDIT, KONDISI KEUANGAN, DEBT DEFAULT, OPINION SHOPPING, LIKUIDITAS, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI GOING CONCERN (Students' Journal of Accounting and Banking, 2013)
The purpose of this study was to obtain empirical evidence about the effect of audit quality, financial condition, debt default, opinion shopping, liquidity and the previous year's audit opinion on going concern opinion. Going concern audit opinion can be used as an early warning for the users of the financial statements in order to avoid mistakes in decision-making.This study took a sample of all companies listed on the Stock Exchange with manufacturing companies listing criteria before 1 January 2006, and did not come out during the years 2006-2011, there were financial statements audited by an independent auditor's report, experiencing negative net profit after tax of at least 2 -year period from 2006 to 2011 financial statements. But once there are 60 companies analyzed. This study uses logistic regression test with a significant level of 5 %. Observations made ​​during the 6 years of the period 2006-2011. The test results prove that the company's financial condition and previous year's audit opinion affect the acceptance of a going concern opinion. While the variable quality of the audit, opinion shopping, liquidity and the debt default does not affect the acceptance of a going concern opinion.Keywords: going concern audit opinion, auditor quality, liquidity, opinion shopping, debt default, previous year's audit opinion, company's financial condition